Integrated thick-film p-i-p+ structures based on spinel ceramics - Klym, H.; Hadzaman, I.; Shpotyuk, O.; Fu, Q.; Luo, W.; Deng, J. (Видавництво Львівської політехніки, 2012)
Multilayered temperature/humidity sensitive thick-film p-i-p+ structures based on spinel-type semiconducting ceramics of different chemical composition Cu0.1Ni0.1Co1.6Mn1.2O4 (with p+-type of electrical conductivity), Cu0.1Ni0.8Co0.2Mn1.9O4 (with p-type of electrical conductivity) and magnesium aluminate i-type MgAl2O4 ceramics were fabricated and investigated. These structures are shown to be successfully applied for integrated environmental sensors.
Keywords: thick films; multilayers; nanostructure; spinel